The Effect of Leaching Times on the Gel Properties of Catfish (Clarias gariepinus) Surimi - Wijayanti, Ima; Santoso, Joko; Jacoeb, Agus M. (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
The effect of leaching times on the proximate composition and gel properties of surimi has been studied in this research. Leaching times significantly influenced the chemical composition of catfish surimi. The raise of leaching times increased the water content and decreased protein, fat and minerals composition of catfish surimi. Water holding capacity value of surimi gel by leaching 3 times increased 29.78% compared to leaching one time. Deformation increased with the rising of leaching times. The highest deformation was  reached by leaching 4 times with raising 74.27% compared to leaching one time. Result of sensory evaluation indicated that the rising of leaching times had positive impact in folding test and teeth cutting test. Three  and four times of leaching produced better characteristics of the gel rather than leaching 1 and 2 times. Keywords: cat fish, gel properties, leaching times, surimi